The Medical Review Panel in Louisiana Neurosurgery and Beyond. Issue 6 (14th August 2019) - Kosty, Jennifer; Jiang, Bowen; LeFever, Devon C; Brougham, Jared R; White, Frederick; Orrico, Katie; Guthikonda, Bharat
Abstract: For the past several decades, medical malpractice claims in the state of Louisiana have been screened by a pretrial medical review panel (MRP). Composed of 3 physicians and 1 attorney, these panels are a method of filtering nonmeritorious lawsuits while expediting creditable claims. Currently, 14 jurisdictions in the United States require medical liability/malpractice cases be heard by an MRP or screening panel prior to trial. In this article, we review the MRP process in Louisiana and compare it to those in other states. Data are presented for the past 10 yr of malpractice claims in Louisiana with an emphasis on the neurosurgery specialty. Finally, the benefits and challenges of pretrial screening panels are discussed.